Interactive Multimedia Based on Augmented Reality for Photosynthesis Material to Improve Science Learning Outcomes of Fourth Grade Elementary School Students - Ni Ketut Sri Asmini; Ni Wayan Rati; Wayan Eka Paramartha (Universitas Pendidikan Ganesha, 2025)
Learning problems in IPAS (Natural and Social Sciences) for fourth-grade students are still dominated by conventional teaching methods and limited interactive learning media, which negatively affect students’ learning outcomes. This study aims to develop, validate, evaluate the practicality, and examine the effectiveness of interactive multimedia based on Augmented Reality (AR) on photosynthesis material to enhance students’ learning outcomes. This research is a type of research and development (R&D) using the ADDIE model. The subjects involved were 13 fourth-grade students for the effectiveness test, 2 teachers for practicality testing, and 2 experts as validators. Data were collected through validation questionnaires, practicality questionnaires, and multiple-choice tests to measure learning outcomes. The data were analyzed using descriptive qualitative and quantitative techniques. The results showed that the AR-based interactive multimedia was declared valid by media experts (3.75) and content experts (3.80), highly practical by teachers (4.00) and students (3.88), and effective in improving learning outcomes with a significance value of 0.000 < 0.05. The findings conclude that AR-based multimedia is a valid, practical, and effective innovation for enhancing students’ IPAS learning outcomes. Its implication suggests potential for broader application in digital-based elementary school learning.